2018
DOI: 10.1039/c7cc09120f
|View full text |Cite
|
Sign up to set email alerts
|

Water transport through graphene oxide membranes: the roles of driving forces

Abstract: Graphene oxide (GO) membranes have shown excellent selectivities in nanofiltration and pervaporation. However, the water transport mechanisms in the unique membrane laminar structure are still not well understood, especially in pervaporation which involves selective permeation and evaporation. Herein, water transport in GO membranes was tested under two different modes: pressure-driven permeation and pervaporation. The pure water flux was found to be 1-2 orders of magnitude higher in pervaporation due to the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 26 publications
5
39
0
1
Order By: Relevance
“…This is probably attributed to the loss of the guest water molecules that could be retained in the GO structure, e.g. water molecules trapped in graphitic domains of GO [25], as well as the water retained in the possible interfacial voids between the GO and PVA matrix. Moreover, there was a weight-loss (between 175-275 ºC) for the MMMs, which was more pronounced as the filler loading increased.…”
Section: Membrane Characterizationmentioning
confidence: 99%
“…This is probably attributed to the loss of the guest water molecules that could be retained in the GO structure, e.g. water molecules trapped in graphitic domains of GO [25], as well as the water retained in the possible interfacial voids between the GO and PVA matrix. Moreover, there was a weight-loss (between 175-275 ºC) for the MMMs, which was more pronounced as the filler loading increased.…”
Section: Membrane Characterizationmentioning
confidence: 99%
“…[10][11] This phenomenon has been widely reported with the d-spacing found to increase from ~0.8 to ~1.3 nm in aqueous environments. [12][13][14][15] Considering the thickness of graphite or well-reduced GO monosheet (ca. 0.34-0.40 nm), [16][17] the 2D nanochannel is accordingly increased from ~0.46 nm to ~0.90 nm.…”
mentioning
confidence: 99%
“…4f). 33 For the GO membranes, it has also been reported that the in-plane oxygen functional groups limit the diffusion of water molecules into the graphene nanochannels due to hydrogen bonds, 34 which further rejects the diffusion of Cs + in solutions into the GO channels, as illustrated in Fig. 4g.…”
Section: Resultsmentioning
confidence: 99%